DIGITAL HR TRANSFORMATION AND ITS INFLUENCE ON EMPLOYEE PERFORMANCE IN LARGE ENTERPRISES - Iwan Lapi; Oktavianti; Rizki Eka Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines digital HR transformation's impact on employee performance in large enterprises. Using a mixed-methods approach combining survey data and case studies, it analyzes adoption patterns across industries. Results show digital tools enhance productivity (90% impact), engagement (85%), and satisfaction through automation and data-driven insights. However, effectiveness is moderated by leadership commitment, organizational culture, and digital literacy, with significant disparities between technology-intensive sectors and regulated industries. The discussion emphasizes that technological implementation alone is insufficient without supportive human factors. The study concludes that successful transformation requires balancing digital capabilities with human-centered change management, ethical governance, and context-sensitive strategies to achieve sustainable performance improvements and prevent widening organizational disparities in the digital era.